Pengukuran Kebahagiaan Remaja: Konstruksi Dan Identifikasi Skala Subjective Well-Being Pada Remaja Di Indonesia - Himawati, Izza (Happiness: Journal of Psychology and Islamic Science, 2020)
The purpose of this study is to develop a measurement for adolescent happiness in Indonesia by focusing on measuring instrument construction techniques and psychometric assessments. This study uses a multi methods, namely a combination of descriptive methods and quantitative methods and consisting of three stages. The first stage is the exploration and theoretical analysis of happiness based on the adolescent development in Indonesia, the second stage is the construction of the psychological scale of happiness, and the third stage is psychometric identification. The psychometric analysis used in this study is the analysis of the reliability and validity of measuring instruments. Alpha-Cronbach technique is used for reliability analysis, and for scale validation using the construct validity test. The form of the scale used in this study is the Likert scale. The results of the psychometric analysis showed that the reliability value was 0.902, the total item correlation coefficient was between 0.375 to 0.702. The conclusion of this research is that in measuring happiness, the stage of development or the age of the individual has a significant influence so that it is necessary to construct a measurement of happiness at each development stage. The results of the analysis show that the validity and reliability of the measuring instrument are psychometrically acceptable and can be categorized according to the research needs and the conditions of the subject.